The Relationship Between Respondents' Characteristics And Quality Of Life In Diabetes Mellitus Patients At The Sipultak Health Center, Pagaran District, North Tapanuli Regency In 2022 - Naibaho , Eka Nugraha V.; Simanjuntak, Agustinus; Silaban, Nataria Yanti; Siburian , Christine Handayani (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Diabetes Mellitus (DM) is a set of symptoms that appear in a person caused by an increase in blood glucose levels due to a progressive decrease in insulin secretion. Diabetes Mellitus will accompany sufferers for a lifetime so that it greatly affects the quality of a person's life. Living with diabetes mellitus can affect his life circumstances which are often referred to as negative influences on the quality of life of sufferers either or without complications. The purpose of the study was to determine the relationship between respondent characteristics and quality of life in diabetes mellitus patients at the Sipultak Health Center, Pagaran District, North Tapanuli Regency in 2022. This type of research is quantitative research with cross sectional. The research was conducted at the Sipultak Health Center, Pagaran District, North Tapanuli Regency in July-August 2022. The study population of Diabetes Mellitus patients was 260 patients. The sample in this study was 73 patients using the Slovin formula. Bivariate analysis using the Chi-Square method. The age characteristics of diabetes mellitus patients are mostly aged 46-55 years as many as 34 people (46.6%). The majority of respondents with diabetes mellitus patients had a good quality of life (score 81-120) as many as 18 people aged 46-55 years with a P.Value value of 0.018<0.05. The sex characteristics of diabetes mellitus patients are mostly male as many as 58 people (79.5%). The majority of respondents with diabetes mellitus patients had a poor quality of life (score 30-80) as many as 32 people in the male sex with a P.Value value of 0.016<0.05. The characteristics of the education level of diabetes mellitus patients are the majority of high school education as many as 23 people (31.5%). The majority of respondents with diabetes mellitus patients had a poor quality of life (score 30-80) as many as 14 people at the college education level with a P.Value value of 0.015<0.05. The job characteristics of diabetes mellitus patients are that the majority work as self-employed as many as 35 people (47.9%). The majority of respondents with diabetes mellitus patients had a poor quality of life (score 30-80) as many as 23 people in the type of work as self-employed with a P.Value value of 0.004<0.05. The characteristics of long-suffering diabetes mellitus patients are the majority of long-suffering from DM for 2-5 years as many as 64 people (87.7%). The majority of respondents of diabetes mellitus patients had a poor quality of life (score 30-80) as many as 38 people who had suffered for 2-5 years with a P.Value value of 0.018<0.05.